The world of ice & fire: the untold history of Westeros and the Game of Thrones (Song of ice and fire, , 1, 2014)
"This is the comprehensive guide to all things Game of Thrones and beyond. From the prehistory to the coming of the First Men, through the reign of the Targaryen kings and Robert's Rebellion, this guide--co-written by George R.R. Martin and the immensely knowledgeable founders and keepers of the www.westeros.org site--will tell series readers old and new all they might want to know about the history and culture of Westeros and the lands beyond the Narrow Sea--a tapestry of all new history that George has invented solely for this volume"--

Fire & blood (Song of ice and fire, , 1, 2018)
The first volume of a definitive two-part history of the Targaryens in Westeros is set centuries before the events of "A Game of Thrones" and answers key questions about the dynasty's origins, conflicts and relationships with dragons. House Targaryen was the only family of dragonlords to survive the Doom of Valyria, and took up residence on Dragonstone. Rehear tales of the legendary Aegon the Conqueror, creator of the Iron Throne. Meet the generations of Targaryens who fought to hold that iconic seat-- from Aegon the Conqueror all the way up to the civil war that nearly tore their dynasty apart. Discover the often bloody-- but always fascinating-- history of Westeros when dragons ruled the skies. -- adapted from jacket
Aegon's conquest , Reign of the dragon: the wars of King Aegon I , Three heads had the dragon: governance under King Aegon I , The sons of the dragon , Prince into king: the ascension of Jaehaerys I , The year of the three brides: 49 AC , A surfeit of rulers , A time of testing: the realm remade , Birth, death, and betrayal under King Jaehaerys I , Jaehaerys and Alysanne: their triumphs and tragedies , The long reign: Jaehaerys and Alysanne: policy, progeny, and pain , Heirs of the dragon: a question of succession , The dying of the dragons: the blacks and the greens , The dying of the dragons: a son for a son , The dying of the dragons: the red dragon and the gold , The dying of the dragons: Rhaenyra triumphant , The dying of the dragons: Rhaenyra overthrown , The dying of the dragons: the short, sad reign of Aegon II , Aftermath: the hour of the wolf , Under the regents: the hooded hand , Under the regents: war and peace and cattle shows , Under the regents: the voyage of Alyn Oakenfist , The Lysene spring and the end of regency , Lineages and family tree.